Synthesis and Thermal-Stability Study of Polybutylene Itaconate Modified with Divinyl Benzene and Glycerol - Atmanto Heru Wibowo; Ninis Makhnunah; Deny Irawati; Candra Purnawan; Nanik Dwi Nurhayati; Henning Storz (Indonesian Journal of Chemistry, 2014)
Polybutylene itaconate (PBI) for modification with divinyl benzene (DVB) and glycerol has been synthesized at 180 °C for 3 h via polycondensation of itaconic acid (IA) and butanediols using catalyst of Ti(OBu)4. Modification on PBI was done with addition of 15%, 20% and 25% DVB (w/w) using benzoyl peroxide. With glycerol, weight variations of glycerol:1,4-butanediol (BDO) in the synthesis were 10%, 30%, and 50% (mole/mole). PBI and PBI modified with DVB and glycerol were characterized with FTIR and TG-DTA. PBI showed a wavenumber shift from 1703 cm-1 to 1728 cm-1 of the C=O functional group from acid to esther. The DVB modification on PBI also showed that the intensity decrease of C=C stretching was due to the formation of crosslinking on the double bond. In the modification with glycerol, three dimensional networking on the polyester occurred through bonding between hydroxyl of glycerol and acid group of IA. Constant intensity of C=C stretching on polyester was seen. The thermal stability of PBI modified with DVB increased, accompanied by rigidity change of the structure. The thermal stability of PBI modified with glycerol decreased, caused by the decrease of regularity degree and the elasticity increase of the three dimensional structure of polyester.